GENDER GAP INDEX FOR EMPLOYMENT OPPORTUNITY - Tewari, Shweta; Chouhan, Rajshree; Sanjeev (International Journal of Engineering Technologies and Management Research, 2017)
Women account for nearly half of the human resources of a nation and play an important role in the socio-economic development of a country. In India, in spite of focus on women empowerment, condition of women at the work place is not very encouraging. Women often face greater barriers than men in terms of securing a decent jobs, wages and conducive working conditions. Provisions relating to women’s work were introduced in 1891, with amendment of the Factories Act, 1881. After independence, number of provisions has been made in the constitutions to protect the welfare of women workers. Number of protective legislations have also been made and implemented by the government for the interest of women workers. The basic objective behind implementation of these legislation are to provide equal and a decent level of remuneration, proper child care center , maternity relief and decent working conditions to women workers. Despite these constitutional and legislative arrangements to reduce gender gap, women in India are facing discrimination at work place and suffer from harassment. The present paper critically reviewed the effectiveness of government policies and legislations framed and enacted for the welfare of women workers. It also examines the gender dimensions of the trends in various aspects of labour market viz. labour force participation rate, workforce participation rate, unemployment rate and wage rate. An attempt has been made to capture the discrimination at work by computing Gender Gap Index using major indicators of labour market. For computing the index, data for the last four decades has been used. The analysis shows that there are gaps in effective enforcement of relevant laws and implementation of women responsive policies. The gender gap index for employment opportunities and the analysis of major employment indicators showed that gender gap is increasing in many aspects. Major indicators of employment such as Labour Force participation rate, Worker population ratio, Unemployment rate and wages now have larger gender gaps than before.